A clinical and pathomechanistic profile of chronic nonbacterial osteomyelitis/chronic recurrent multifocal osteomyelitis and challenges facing the field. (September 2013) - Hedrich, Christian M; Hahn, Gabriele; Girschick, Hermann J; Morbach, Henner
Sporadic chronic nonbacterial osteomyelitis (CNO) is the most common auto-inflammatory bone disorder. The clinical picture is highly variable ranging from nonsymptomatic monofocal lesions to chronic recurrent multifocal disease. Symptoms include pain, local swelling and warmth in the absence or presence of fever. A subset of CNO patients exhibits additional symptoms of psoriatic skin involvement, palmoplantar pustulosis and inflammatory bowel disease. Novel insights into the pathogenesis of CNO link the failure to produce IL-10 and the resulting imbalance toward pro-inflammatory IL-6 and TNF-α with disease expression. Treatment is empiric and includes NSAIDs, corticosteroids, sulfasalazine, methotrexate, TNF inhibitors and bisphosphonates. Laboratory studies and clinical trials are warranted to: establish biomarkers that predict flares and clinical outcomes, identify patients that require additional treatment on top of NSAIDs, establish evidence-based treatment regimens, allow a risk–benefit assessment for the available therapeutic strategies, and identify novel therapeutic targets.